On Changes in Complex Sentences Syntax in the Russian Language of the 17th Century (on Material of Siberian Petitions) - L. A. Inyutina; T. S. Shilnikova (Научный диалог)
The article deals with the problem of forming grammatical (syntactic) norms of the Russian national language based on the material of Siberian monuments of business writing of the 17th century. Relevance of the work is determined by the fact that Russian syntax and the history of the Russian language in Siberia are insufficiently studied, as well as by the need to expand the source base of such research. Scientific novelty of the work consists in the study of historical syntax of the complex sentences in the texts of Siberian petitions, most of which are not published and has not previously been brought to the historical-grammatical research. The high source value and linguistic informativeness of the Siberian petitions of the 17th century are proved. These texts analyze complex sentences with paratactic and hypotactic connections. The article traces the peculiarities of their use in monuments of local business writing in the aspect of developing syntactic norms of the Russian national language. The arsenal of compositional and subordinate conjunctions used in such sentences is defined. The changes in the structure of complex sentences are found out. They reflect live folk speech, language consciousness of the Russian people in Siberia and at the same time they are typical for the syntactic system of the Russian national language in the initial period of its formation.